Business without management MacIntyrean accounting, management, and practice-led business - West, Andrew (2025)
Alasdair MacIntyre's critique of managerial capitalism is well known, with some arguing that MacIntyrean thought is antithetical to contemporary capitalist business. Nevertheless, substantial efforts have been taken to demonstrate how different business activities constitute MacIntyrean practices, which points to an incoherence at the heart of MacIntyrean business ethics scholarship. This article proposes a way of bridging these perspectives, suggesting a reimagined MacIntyrean approach to business that is thoroughly 'practice-led.' A detailed comparison of accounting and management shows that while neither are practices in 'good order,' they differ in significant ways: where management does not meet the criteria for a MacIntyrean practice, accounting is a 'distorted' practice. This leads to a categorisation of practice-led business activity, whereby the traditional tasks of management are subsumed, shared or subordinated to practices and practitioners. Insights on how this can be implemented are drawn from the 'communities of practice' literature and a consideration of professions.
Keywords: MacIntyre; Accounting; communities of practice; Management; Practice; Virtue Ethics; Aufsatz in Zeitschrift